Airbnb, buy-to-let investment and tourism-driven displacement: a case study in Lisbon - Cocola-Gant, Agustín (2019)
Through detailed empirical analysis of a central area of Lisbon, the paper explores whether short-term rental platforms such as Airbnb channel investment in residential real estate and the way in which the local community is affected by the proliferation of apartments rented to visitors. Between 2015 and 2017 we conducted fine-grained fieldwork in the historical neighborhood of Alfama and identified both the producers and socio-spatial consequences of short-term rentals. Our research did not find evidence of a sharing economy. Rather, it found a process of buy-to-let investment in which different players make profits from rents and displace residents with tourists. The paper develops two main arguments: first, we suggest that Airbnb acts as an instrument that contributes to the financialization of housing. Compared to the traditional rental market, short-term rentals offer a number of benefits that enhance market efficiency for property owners, making them increasingly attractive for both local and global investors. We found that the suppliers of short-term rentals are primarily investors that use housing as an asset to store capital. The main advantage of the short-term rental market for investors is that while they can make profits by renting properties to visitors they can also sell them tenant-free at any moment. Second, Airbnb gives way to a hyper-flexible rental market that for tenants implies increasing insecurity and displacement concerns. We portray Airbnb as an example of buy-to-let gentrification that is experienced by residents as a process of social injustice.